Modeling and tuning of the active power control loop in a power plant (Ciencias de la Ingeniería y Aplicadas, 2025)
The MAN engine generator set (a German internal combustion engine manufacturer) with a maximum rated power of 184 MW, located in the city of Moa, Holguín province, is one of the power plants connected to the SEN (National Electric Power System), contributing 165 MW to the system's demand. The generators' active power is regulated by the fuel input to the internal combustion engine, which rotates at a speed of 514 rpm, accelerating or decelerating. The control loop, tuned by trial and error, consists of current and voltage transformers, a PLC (Programmable Logic Controller), and an actuator to manipulate fuel flow. Over the years of operation, the company's engines have suffered wear in their fuel regulation mechanisms, resulting in power fluctuations and losses of up to 2 MW. This article proposes parametric models that describe the system dynamics. Passive experiments were conducted over 10 operational days to model the behavior of engine power relative to the position of the actuator that manipulates fuel flow. As a result, parameters for automatic controllers were proposed to optimize energy consumption, minimize friction losses or thermal inefficiencies, improve combustion efficiency, and reduce pollutant emissions
Keywords: Electric Power System; active power; generators; parametric models; automatic controllers